Detection of atrial fibrillation in patients with embolic stroke of undetermined source by prolonged monitoring with implantable loop recorders - Israel, Carsten; Kitsiou, Alkisti; Kalyani, Malik; Deelawar, Sameera; Ejangue, Lucy Ekosso; Rogalewski, Andreas; Hagemeister, Christoph; Minnerup, Jens; Schäbitz, Wolf-Rüdiger (Thrombosis and Haemostasis, 2017)
Recently, the clinical entity embolic stroke of undetermined source (ESUS) has been defined for patients with ischemic strokes, where neither a cardioembolic nor a non-cardiac source can be detected. These patients may suffer from asymptomatic atrial fibrillation (AF), terminating spontaneously and thus eluding detection. Implantable loop recorders (ILR) with automatic AF detection algorithms can detect short-lasting, subclinical AF. The aim of this study was to prospectively assess and predict AF detection in patients with ESUS using ILR with daily remote interrogation. Patients with acute ESUS received an ILR, were seen every 6 months and additionally interrogated their ILR daily using remote monitoring. The incidence of AF detection was assessed and parameters which might predict AF detection (clinical and from magnetic resonance tomography) were analysed. ILR implantation was performed in 123 patients on average 20 days after stroke. During a mean follow-up of 12.7±5.5 months, AF was documented and manually confirmed in 29 of 123 patients (23.6%). First AF detection occurred on average after 3.6±3.4 months of monitoring. Patients with AF were on average older, had a higher CHA2DS2-VASc score and more often cerebral microangiopathy. In conclusion, AF can be documented in approximately 25% of patients with the diagnosis of ESUS after careful work-up within a year of monitoring by an ILR and daily remote interrogation. This had important therapeutic consequences (initiation of anticoagulation for secondary stroke prevention) in these patients.
Keywords: Atrial fibrillation; embolic stroke of undetermined source; implantable; loop-recorder; remote monitoring; stroke